Development of a self-propelled compost turning machine for composting oil palm empty fruit bunches - Mohamad Shukery, Mohamad Firdza (2011)
As a better way of utilizing agricultural waste and reducing fertilizer cost, the rich nutrient of empty fruit bunches (EFB) could be used in the production of compost and returned back to the soil as bio-organic fertilizer. However, the present turning machines that been employed in the production of EFB compost are unsuitable to employ due to the characteristic of EFB. The EFB are fibrous with high lignin and bulky in size giving higher tendency for the material to entangle and finally stalled the rotational rotor of turning machine. In addition, these turning machines are huge in physical size and engine capacity, high operation cost, and generally designed to work on animal and general agriculture wastes with have different properties from EFB. With current high fertilizer cost, abundant amply of EFB, utmost benefits of using organic fertilizers, and the unavailable of proper turning machine for EFB, it thus necessary for the oil palm plantation industry in Malaysia to be provided with a proper compost turning machine to produce compost from the EFB. A self-propelled turning machine for windrow composting of empty fruit bunches (EFB) had been designed, developed and tested. Conceptual design of the machine has been drawn in 2-D and 3-D drawing. Estimation of engine power requirement of the developed turning machine and computations of total hydraulic pressure to operate all actuators within the hydraulic system are also determined. A 60 kW diesel engine was used as the power source to generate hydraulic driven tires, hydraulic driven rotor and blade assembly and power steering system. The overall size of the machine was 1700 mm in length, 3600 mm in width and 3000 mm in height. Total weight of the developed turning machine was 3.83 tonne. The developed compost turning machine was designed to work with maximum windrow size of 2500 mm in width and 1500 mm in height. The rotor size was 2500 mm in length and 275 mm in diameter excluded the blade. The rotor contains a total of 30 blades that make-up of 25 straight blades at the center portion and 5 inclined tip blades placed at end portion of the rotor. All these blades were at 90º upright position and evenly placed in a spiral order at 70º direction towards to the centre of rotor so that the windrow will be rebuilt during the turning operation. The developed compost turning machine designed to overcome most of turners faced at the side which were flexibility in movement and transportation. The steering system of the machine has been design with capability to turn the wheels in 90°. This rare mechanism in the turner enables the machine to move sideway especially in the limited space. Data from field evaluation shows that the developed self-propelled compost turning machine was able to demonstrate functions as windrow turner under an actual composting production of EFB. The mean actual velocity of turning machine during the test was 7.78 cm/s with mean wheel slippage of 36. 87 %. The mean mas throughput capacity of the turning machine was 84.83 tonne/hr and total mass production of composting plot was 47.29 tonne/hr. The mean C/N ratio of EFB reduced from 66.30 to 29.34 or about 55.57% at the week-12 of composting period. The developed self-propelled compost turning machine showed high potential to be used in windrow composting for empty fruit bunch (EFB) as another step forward to empowering oil palm industry in Malaysia.